The Business Model of Social Entrepreneurship in Indonesia - Kusumasari, Bevaola (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
The purpose of this study is to develop a conceptual setting in which the business models of social enterprises can be analyzed through value proposition, value creation and value capture. This study employed a method of qualitativeresearch through in-depth interviews of 30 social entrepreneurships in Jakarta, Yogyakarta, Bandung and Bali. The result of the study showed that, in terms of the value proposition in business models of entrepreneurship, all organizations areestablished in response to discriminations suffered by marginal communities. Regarding the aspect of value capture, it seems to appear through a series of activities such as conducting humanity-based programs, capacity building and holding educationand training on the environment. Value creation is found in cases where the more benefits the community gains from program implementation, the more successful and sustainable the social entrepreneurship will be. This research proposes a new typeof business model that aims to categorize and explain business model innovations for sustainability, provides mechanisms to assist the innovation process for embedding sustainability in business models and defines a clear agenda for business modelsfor sustainability. Based on the empiric data, this study successfully identified four types of social entrepreneur models in Indonesia which are based on the mapping results found in all of the organizations aiming to resolve social, economic, andenvironmental issues in Indonesia. This study successfully identified four types of business models: Mixed-based Model, Sharia-based Model, Volunteerism-based Model, and Cooperation-based Model.